2019
DOI: 10.1080/10717544.2019.1568624
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small micelles based on polyoxyl 15 hydroxystearate for ocular delivery of myricetin: optimization, in vitro, and in vivo evaluation

Abstract: 2019) Ultra-small micelles based on polyoxyl 15 hydroxystearate for ocular delivery of myricetin: optimization, invitro, and invivo evaluation, Drug Delivery, 26:1, 158-167, ABSTRACT The aim was to develop a nanocarrier based on polyoxyl 15 hydroxystearate (KolliphorV R HS15, HS15) micelles for the solubility, stability, and ocular delivery of myricetin (Myr). An optimized ratio of HS15 and Myr was prepared to fabricate HS15-Myr micelle ophthalmic solution. Myr-encapsulating HS15 micelles (HS15-Myr micelles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Hou et al [ 61 ] studied the antioxidant effect of HS15-Myr micelles and independent myricetin by using FRAP (ferric reducing antioxidant power) and ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) assays. The ABTS assay displayed an improved value from 22.20 to 41.77% in HS15-Myr micelles and 0 to 6.12% in independent myricetin at two different concentrations and incubation periods.…”
Section: Preclinical Pharmacological Activities Of Myricetinmentioning
confidence: 99%
“…Hou et al [ 61 ] studied the antioxidant effect of HS15-Myr micelles and independent myricetin by using FRAP (ferric reducing antioxidant power) and ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) assays. The ABTS assay displayed an improved value from 22.20 to 41.77% in HS15-Myr micelles and 0 to 6.12% in independent myricetin at two different concentrations and incubation periods.…”
Section: Preclinical Pharmacological Activities Of Myricetinmentioning
confidence: 99%
“…Though many researchers explored ocular delivery with micelle formulation, most of their explored nanomaterials were not authorized pharmaceutical excipients, and the ocular biocompatibility of these materials has been the subject of debate (Song et al., 2018). An ultra-small nanocarrier based on polyoxyl 15 hydroxystearate (Kolliphor ® HS15, HS15) micelles was explored to evaluate the formulation potential of Myr to ocular topical administration in previous report (Hou et al., 2019). Though the in vivo ocular tolerance tests revealed that the micelle formulations based on HS15 showed excellent ocular tolerance (Zhou et al., 2017; Hou et al., 2019), the ocular safety concerns of HS15 and its formulation should be kept in mind, and a recent publication also hinted the safety concern of this nonionic surfactant HS15 used in drug delivery formulations (Cavanagh et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(The t 1/2 of Myr in the PVCL-PVA-PEG micelle solution was 2.61-, 3.93-, 7.48-, 19.20-, 34.28-, and 36.43-fold higher than that of Myr in the HS15 micelle solution with pH values of 6.0, 6.2, 6.5, 6.8, 7.0, and 7.4, respectively. Data were calculated from this article and our previous report (Hou et al., 2019). ) The ultra-low CMC of PVCL-PVA-PEG might contribute this high potential of improvement of Myr’s chemical stability (the CMC of PVCL-PVA-PEG was 3.68 × 10 −8 M, and HS15 was 1.16 × 10 −3 M in artificial tears; Guo, Zhang et al., 2015; Hou et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations